Dakwah Virtual: Internet sebagai Reaktualisasi Sistem Komunikasi Dakwah di Era Digital - Andriani, Astri Dwi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2023)
This investigate points to decide graphic information with respect to the part of the web as a re-actualization of the da'wah communication framework within the advanced time. The sort of investigate utilized in this talk is utilizing library inquire about or writing audit which incorporates: efficient recognizable proof, examination of data on reports containing data related to the ponder issue. The information collection strategy that analysts utilized was the documentation strategy, to be specific searching for information with respect to things or factors within the frame of books, daily papers, diaries, and so on. With the presence of the web, the boundaries of separate and time that utilized to be impediments are presently beginning to blur. As a result, people can associated in nearly all corners of the world, without separate. With respect to devout life, with the rise of the web and social media, references to devout information put the web as a reference. With the web, references to devout information gotten to be more open. Within the end, the web got to be a modern medium for Muslims to get to references to the devout life of Muslims. The suggestion of this inquire about is to supply expressive information with respect to the transformation process of Islamic da'wah. This will be seen from the rise of cyber da'wah talk, the improvement of online Islamic writing, and amar ma'ruf nahi munkar exercises within the computerized domain.